Lithuania Minor and Prussia on the old maps (1806–2008) - Lukoševičius, Viktoras (Geodesy and Cartography, 2013)
While continuing researches on ancient cartography (Lukoševičius 2013) the publication is aimed at viewing maps of Lithuania Minor and Prussia in the perspective of historical events, with a special emphasis on most important historical events as well as cartography development moments. The method used is analysis of different maps, by different authors, found in cartographical archives. The article presents the authors and designers 48 maps of Lithuania Minor and Prussia and discusses map characteristics. It also provides links that are helpful for the readers interested in a more detailed studies of specific maps. Summarizing research results the authors conclude that ancient maps where Lithuania Minor is marked are true historical witnesses helping to understand long and complicated formation process of Lithuania Minor and the state of Lithuania; however the analysis alone is insufficient to fully reveal its historic concept.